Seawater carbonate chemistry and biosynthesis of polyunsaturated fatty acids in a benthic harpacticoid copepod - Jens Boyen; María T Rodríguez; Bruno Vlaeminck; Patrick Fink; Pascal I Hablützel; Marleen De Troch (PANGAEA, 2025)
In this study, we conducted a laboratory experiment to evaluate the combined effects of warming (+3 9°C), acidification (0.4 pH), and dietary LC-PUFA deficiency on the fatty acid composition and LC-PUFA biosynthesis (measured by quantitative RT-PCR) of the benthic harpacticoid copepod Platychelipus littoralis (Brady, 1880). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-03-24.